The influence of roller burnishing process parameters on surface quality and fatigue life of AA 7075‐T6 alloy. Issue 5 (5th May 2022) - Celik, M.; Caydas, U.; Akyuz, M.
Abstract: Roller burnishing method is a low‐cost and effective surface treatment method that has been frequently preferred in recent years. In this method the surface roughness is minimized by small plastic deformations, without removing chips from the surfaces, caused by the rolling element pressed against the surface with a certain force. While the surface hardness of the material increases in the process, the surface roughness decreases significantly. In this study, the effects of the process parameters of roller burnishing method (burnishing pressure and number of passes) on AA7075‐T6 aluminum alloy in terms of fatigue strength and surface roughness were investigated experimentally. Taguchi L9 experimental design method was used in the study, and the burnishing process was carried out by a specially produced disc‐shaped apparatus. As a result of the study, it was determined that the roller burnishing method increased both the fatigue strength and surface quality of AA 7075 T6 alloy. In consequence of roller burnishing, it was determined that fatigue life and surface roughness values improved by 116 % and 96 %, respectively. Abstract : In this study, it was aimed to improve the surface quality and fatigue life of AA 7075‐T6 alloy by roller burnishing method. As a result of the study, the surface quality and fatigue life were improved by an average of 96 % and 116 %, respectively. Translation abstract: Das Rollierverfahren ist ein kostengünstiges und effektives Oberflächenbehandlungsverfahren, das in den letzten Jahren häufig bevorzugt wurde. Bei diesem Verfahren wird die Oberflächenrauigkeit durch kleine plastische Verformungen minimiert, ohne mit Hilfe des mit einer gewissen Kraft gegen die Oberfläche gepressten Wälzkörpers Späne von den Oberflächen zu entfernen. Während die Oberflächenhärte des Materials dabei zunimmt, nimmt die Oberflächenrauheit deutlich ab. In dieser Studie wurden die Auswirkungen der Prozessparameter des Rollierverfahrens (Glättdruck und Anzahl der Durchgänge) auf die Aluminiumlegierung AA7075‐T6 in Bezug auf Dauerfestigkeit und Oberflächenrauheit experimentell untersucht. In der Studie wurde die experimentelle Entwurfsmethode Taguchi L9 verwendet, und der Polierprozess wurde mit einer speziell hergestellten scheibenförmigen Apparatur durchgeführt. Als Ergebnis der Studie wurde festgestellt, dass das Rollierverfahren sowohl die Dauerfestigkeit als auch die Oberflächenqualität der Legierung AA 7075 T6 erhöht. Als Folge des Rollierens wurde festgestellt, dass sich die Ermüdungslebensdauer und die Oberflächenrauheitswerte um 116 % bzw. 96 % verbesserten.